Cisco FirePOWER and Advanced Malware Protection : LiveLessons (LiveLessons (Indianapolis, Ind.), 2017)
"Learn how Cisco Advanced Malware Protection (AMP) capabilities have been integrated into the Cisco ASA with FirePOWER Services and Firepower Threat Defense. Cisco Firepower and Advanced Malware Protection LiveLessons walks you through the steps for designing, configuring, and troubleshooting Cisco ASA Firepower services so you can implement latest threat detection services from Cisco. Omar Santos, best-selling author of CCNA Security Cert Guide and Complete Video Course and a principal engineer of the Cisco Product Security Incident Response Team (PSIRT), provides step-by-step coverage of the new Cisco Firepower services and explores the Cisco Next-Generation IPS appliances, Cisco ASA with Firepower services, AMP for networks, endpoints and content security, and Firepower Management Center."--Resource description page.